Teaching Spoken Narrative by Using Silent Viewing Video Technique to Senior High School Students - Ana Muslimah (Bina Nusantara University, 2018)
This research aimed to describe the implementation of silent viewing technique in teaching speaking narrative to develop students’ ideas in learning process. There were 34 senior high school students in SMAN 1 Driyorejo who participated in this qualitative study. This research used three instruments such as checklist observation, interview, and questionnaire. The result shows that the use of silent viewing technique is successful and effective. The students can make good storytelling after the implementation. It also makes the students easily absorb the new knowledge and share their ideas and opinions based on what they have watched in the silent video.